1995
DOI: 10.1002/hed.2880170406
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the ethmoid sinus

Abstract: Obtaining clear margins by craniofacial resection is essential to the management of adenocarcinoma of the ethmoid sinuses. Radiotherapy is reserved for positive margins, cribriform plate penetration, dural invasion, and high-grade lesions that are close to the cribriform plate. Local control was obtained in 87% of our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
1
18
1
1
Order By: Relevance
“…The majority of these carcinomas originate in the maxillary sinuses. Primary ethmoidal carcinomas account for only 20% of all paranasal sinus malignancies [2, 3, 4, 5], with adenocarcinomas accounting for just 4% of all malignancies of the nose and sinuses, but for 40% of all carcinomas of the ethmoid sinuses [6, 7]. Because of the rarity of both a diagnosis of primary oncocytic adenocarcinoma of the ethmoid, and the orbital presentation, we have reported the following case.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of these carcinomas originate in the maxillary sinuses. Primary ethmoidal carcinomas account for only 20% of all paranasal sinus malignancies [2, 3, 4, 5], with adenocarcinomas accounting for just 4% of all malignancies of the nose and sinuses, but for 40% of all carcinomas of the ethmoid sinuses [6, 7]. Because of the rarity of both a diagnosis of primary oncocytic adenocarcinoma of the ethmoid, and the orbital presentation, we have reported the following case.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant presenting symptoms of ethmoidal sinus adenocarcinoma are epistaxis and nasal obstruction [2, 6, 8]. The orbit lies lateral to the ethmoid sinus and is separated from the sinus by the medial orbital wall and its periosteum, making it difficult for tumour to spread directly to the orbit.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Epithelial tumours represent over two/third of the SNC and, among them, the most common histotypes are adenocarcinoma and squamous cell carcinoma (SCC) (2) with European studies showing a frequency of adenocarcinoma (3)(4)(5) higher than that reported in the corresponding Northern American studies (6,7) . Other less common sinonasal epithelial histologies are adenoid cystic cancer (ACC) and undifferentiated carcinoma (SNUC).…”
Section: Introductionmentioning
confidence: 99%